SISP practices, approaches, contexts and performance of government agencies in Malaysia / Hisyam Harun and Mohd Khairuddin Hashim - Harun, Hisyam; Hashim, Mohd Khairuddin (Faculty of Administrative Science and Policy Studies, 2012)
Strategic information system planning (SISP) is essential to both the operations as well as the performance of organizations. Viewed as a practice and process, SISP has gained approval and recognition from both public and private organizations. Notwithstanding, the attraction and attention on SISP, a review of previous studies suggests that SISP as an area of research has not received much research emphasis as deserved. Despite various research issues been highlighted in the area, limited studies have attempted to address these issues. As a result, not much is still known about SISP. This study represents an attempt to investigate the relationships between SISP practices, approaches, contexts and performance of government agencies. The data for the study were collected from 54 government agencies by using structured questionnaire. Results of the analyzed data indicate that SISP practices are positively related to performance. In addition, the results also show that SISP approaches and contexts moderate the relationships between SISP practices and performance of the government agencies that participated in the study.